Manipulable Congestion Tolls - Jan K. Brueckner; Erik T. Verhoef (Tinbergen Institute, 2009)
The recent literature on congestion pricing with large agents contains a remarkable inconsistency: though agents are large enough to recognize self-imposed congestion and exert market power over prices, they do not take into account the impact of their own actions on the magnitude of congestion tolls. When large agents are confronted with tolls derived under this parametric assumption but understand the rule used to generate them, the toll system will no longer guide the market to the social optimum. To address this problem, the present paper derives alternate, manipulable toll rules, which are designed to achieve the social optimum when agents anticipate the full impact of their actions on toll liabilities.
Keywords: R41; R48; D62; 330; Congestion pricing; market power; aviation; Internalisierung externer Effekte; Straßenbenutzungsgebühr; Bottleneck; Wohlfahrtstheorie; Theorie